Challenges of Employing Interactive Simulations in Teaching Science Subject to Intermediate and Secondary Levels from the Viewpoint of Science Teachers in Madinah - Alharbi, Hanaa Eid; Alofi, Basimah Saleem (Journal of Educational and Psychological Sciences, 2023)
The aim of this research is to uncover the most prominent challenges in employing interactive simulations in science teaching for the intermediate and secondary levels from the viewpoint of science teachers in Madinah, and to investigate their recommendations that could contribute to the success of its employment in science teaching. To achieve these goals, a questionnaire was used as a research tool. The research sample was chosen by the stratified random method, which reached (120) science teachers. The results of this study showed several challenges facing the use of interactive simulation in science teaching, the most prominent of which was related to the preparatory aspects. Science teachers suggested some recommendations for achieving the success of employing interactive simulations in teaching science. Based on the research findings, the researcher recommends facilitating access to interactive simulation software to be employed in science education by providing computers in science laboratories.
Keywords: Interactive Simulation Programs; Interactive Computer Programs; Science Education; Simulation